Authority Of Regional Governments In Establishing Regional Regulations Relating To The Field Of Community Welfare - Prasista Maolana (Faculty of Law, Muhammadiyah University of Surabaya, 2022)
Research regional aims to produce regulations that responsive in support implementation of This So implementation autonomy regional does rise problems new that can hinder .development growth to of the that in research law used several among approaches ,others ;this approach primary legislation Law No.32 Year 2004 concerning Autonomy Regional and Law 12 Year 2011 concerning formation regulations .legislation Or approach another is being approached in an case approach historical approach comparative and approach conceptual local government district in, running ,government ,has authority legislative same time authority executive. Authority legislative government regional regency as one of institutions forming regulations regional regency must icarried out based on principles formation regulations legislation, principles immaterial content attention limitation scope material content to regulationarea regency and not conflict with interest public or which regulation legislation ,is ,do hierarchical is higher. Authority executive government region regency ione which is implement regulations region .regency Regulation area district has role important for government iregion idistrict iin iadministering iaffairs government area district related to administration welfare for.region anKeywords: legislation, authority, carried